2007
DOI: 10.1017/s0022112007006374
|View full text |Cite
|
Sign up to set email alerts
|

Mass flow rate measurements in a microchannel, from hydrodynamic to near free molecular regimes

Abstract: International audienceHelium mass flow rates in a microchannel were measured, for a wide Knudsen-number range, in isothermal steady conditions. The flow Knudsen numbers, considered here, cover the range from continuum slip regime to the near free molecular regime. We used a single-channel system involved in an experimental platform more powerful than those previously used. The experimental errors and uncertainties were accurately investigated and estimated. In the continuum slip regime, it was found that the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
169
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(180 citation statements)
references
References 27 publications
10
169
0
1
Order By: Relevance
“…Ewart et al studied the flow of monatomic gases through rectangular microchannels with a low-aspect ratio a* = 2% (Ewart 2007;Ewart et al 2007). With such an aspect ratio, the flow is close to a 2-D flow between parallel plates.…”
Section: Experimental Data For Single Monatomic Gasesmentioning
confidence: 99%
“…Ewart et al studied the flow of monatomic gases through rectangular microchannels with a low-aspect ratio a* = 2% (Ewart 2007;Ewart et al 2007). With such an aspect ratio, the flow is close to a 2-D flow between parallel plates.…”
Section: Experimental Data For Single Monatomic Gasesmentioning
confidence: 99%
“…Therefore, extensive experimental and theoretical works have been conducted (see Knudsen (1909); Edmonds & Hobson (1965); Porodnov et al (1974Porodnov et al ( , 1978; Ewart et al (2007); RojasCárdenas et al (2013); Yamaguchi et al (2014Yamaguchi et al ( , 2016; Sharipov (2011) and references therein) to quantify the influence of gas-surface interaction and test the applicability of the BC: most of the time, the Maxwell model is tested (Porodnov et al 1978;Ewart et al 2007;Yamaguchi et al 2016), and the Cercignani-Lampis model is checked for a few cases (Cercignani & Lampis 1971;Sharipov 2003b). The use of the Maxwell model is not satisfactory, since in Poiseuille flow it has been seen that the TMAC has to be adjusted at different range of the rarefaction parameter (Ewart et al 2007), while in thermal transpiration flow (Yamaguchi et al 2014(Yamaguchi et al , 2016) neither the Maxwell model nor the Cercignani-Lampis model can recover the MFR and thermomolecular pressure difference (TPD, a parameter indicating the performance of the Knudsen pump) exponent simultaneously, see § 5.1 below.…”
Section: Introductionmentioning
confidence: 99%
“…Knudsen's experimental work in the transition flow regime [2] revealed that there is a minimum in the normalized mass flow rate G [4]. This is referred to as the Knudsen paradox in the literature, as the classical Navier-Stokes solution with no-slip boundary conditions fail to predict this phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…Behaviour of isothermal rarefied gases can be described by the Boltzmann equation [3], and the mass flow rate over the full range of Knudsen number predicted [4]. However, solution methods require an assumption on the local pressure that does not allow an investigation of the actual pressure profile [3,4].…”
Section: Introductionmentioning
confidence: 99%